PENGARUH ASUHAN KEBIDANAN BERBASIS CONTINUITY OF CARE DI TPMB DELIMA WM KOTA BANJARMASIN - Wahdah, Rabia (Midwifery And Complementary Care, 2023)
Background: Comprehensive obstetric care is the care provided by midwives from pregnancy, childbirth, newborns, postpartum and intermediate periods, infants, healthy toddlers and reproductive periods which aim to provide quality health services in an effort to reduce AKI (Maternal Mortality Rate) and AKB (Infant Mortality Rate) (Ofori et al., 2020). Another effort made to reduce maternal mortality and infant mortality is to encourage every delivery to be assisted by trained health workers, namely obstetricians and gynecologists (SpOG), general practitioners, and midwives, and efforts to be carried out in health care facilities (Tengah, 2019). The impact that can occur if pregnancy, childbirth, postpartum, BBL, and family planning are not properly cared for, it will cause various complications. With the continuity of care service, it is hoped that more women will get these services. tend to receive effective services, more efficient experiences, and better quality clinical outcomes (Ningsih, 2017). Objective:. Providing obstetric care in a continuity of care (continuous) during pregnancy, childbirth, postpartum, BBL and family planning using the SOAP approach at TPMB Delima WM in 2022. Methods: The method used in this study is using the COC (continuity of care) research method, which is an approach method starting from pregnancy, childbirth, postpartum, to BBL. In this study, a descriptive research method is used and the type used is a case study.Result: Case analysis in mothers by Continuity of Care (COC) from pregnancy, childbirth, postpartum, newborn (BBL), and family planning at TPMB WM. The care obtained by mothers is in accordance with the standards of midwifery care, there is no gap between the care provided and the existing theory. Keywords: Implementation, Midwifery Care, COC (Continuity Of Care)